Anal Sphincter Augmentation Using Biological Material - Alam, Nasra N.; Narang, Sunil K.; Köckerling, Ferdinand; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2015)
Introduction The aim of this review is to provide an overview of the use of biological materials in the augmentation of the anal sphincter either as part of an overlapping sphincter repair (OSR) or anal bulking procedure. Methods A systematic search of PubMed was conducted using the search terms ‘anal bulking agents’, ‘anal sphincter repair’ or ‘overlapping sphincter repair’. Five studies using biological material as part of an overlapping sphincter repair (OSR) or as an anal bulking agent were identified. Results 122 patients underwent anal bulking with a biological material. Anorectal physiology was conducted in 27 patients and demonstrated deterioration in maximum resting pressure, and no significant change in maximum squeeze increment. Quality of life scores (QoLs) demonstrated improvements in scores at 6 weeks and 6 months, but this had deteriorated at 12 month follow up. Biological material was used in 23 patients to carry out an anal encirclement procedure. Improvements in QoLs were observed in patients undergoing OSR as well as anal encirclement using biological material. Incontinence episodes decreased to an average of one per week from 8 to 10 preoperatively. Conclusions Sphincter encirclement with biological material has demonstrated improvements in continence and quality of life scores in the short term compared to traditional repair alone. Long-term studies are necessary to determine if this effect is sustained. As a bulking agent, benefits are short-term.